2015
DOI: 10.1098/rsos.150521
|View full text |Cite
|
Sign up to set email alerts
|

The cervical anatomy of Samotherium , an intermediate-necked giraffid

Abstract: Giraffidae are represented by many extinct species. The only two extant taxa possess diametrically contrasting cervical morphology, as the okapi is short-necked and the giraffe is exceptionally long-necked. Samotherium major, known from the Late Miocene of Samos in Greece and other Eurasian localities, is a key extinct giraffid; it possesses cervical vertebrae that are intermediate in the evolutionary elongation of the neck. We describe detailed anatomical features of the cervicals of S. major, and compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Mitchell and Skinner (2003) implied that throughout the giraffe fossil record, there is clear evidence for stepwise neck elongation. This idea is strongly supported by recent studies quantifying the length of cervical vertebrae (Badlangana et al, 2009;Danowitz et al, 2015aDanowitz et al, , 2015b during phylogenetic evolution (Hamilton, '78;Solonias, 2007). These studies conducted a comprehensive survey of the specimens from all seven subfamilies including extant species as well as fossils.…”
Section: Case Study 1: the Giraffe's Long Neckmentioning
confidence: 69%
“…Mitchell and Skinner (2003) implied that throughout the giraffe fossil record, there is clear evidence for stepwise neck elongation. This idea is strongly supported by recent studies quantifying the length of cervical vertebrae (Badlangana et al, 2009;Danowitz et al, 2015aDanowitz et al, , 2015b during phylogenetic evolution (Hamilton, '78;Solonias, 2007). These studies conducted a comprehensive survey of the specimens from all seven subfamilies including extant species as well as fossils.…”
Section: Case Study 1: the Giraffe's Long Neckmentioning
confidence: 69%
“…Recent research on the cervical anatomy and evolution of Giraffidae demonstrated that neck elongation and secondary shortening clearly fits on the backdrop of an evolutionary scheme; the primitive giraffids exhibit generally elongated vertebrae, the sivatheres possess features representing neck shortening, the palaeotragines display vertebrae with cranial elongation, and the two species of Giraffa exhibit vertebrae that are elongated cranially and caudally (Danowitz et al, 2015b). In addi- tion, morphological studies on the neck of Samotherium show that the cervical features are intermediate between those of the giraffe and the okapi, which reflects its phylogenic position between the two extant taxa (Danowitz et al, 2015a). Skull features classically demonstrate phylogenetic patterns, as do neck morphologies; metapodials are apparently more complex and do not clearly fit the established relationships.…”
Section: Giraffa Camelopardalismentioning
confidence: 74%
“…In giraffid evolution, neck elongation occurs in three stages; general vertebral elongation precedes the start of the Giraffidae, cranial elongation occurs around the start of the samothere lineage, and caudal elongation allows for the extreme elongation of the modern giraffe [5]. Overall, the third cervical vertebra of Samotherium boissieri and Schansitherium tafeli are relatively similar, and they differ in five of the total sixteen vertebral elongation characters that were scored.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebra was evaluated and the terminology we use is based on the following studies: Danowitz and Solounias [24]; Danowitz et al [5, 25]. Table 3 summarizes the morphology.…”
Section: Description Of Schansitherium Tafeli (Tables 1 and 2 Summarimentioning
confidence: 99%